Scientific Publications’ Bibliometric Analysis of Application-Level TCP/IP Models’ Communication Protocols for the Internet of Things - O. Borysov (Вісник Харківської державної академії культури)
A bibliometric analysis of publications on application-layer communication protocols in the context of the Internet of Things technologies have been conducted. The study highlights significant disparities in scientific attention given to various protocols, emphasizing the dominance of MQTT and CoAP in the scientific literature. Data from the Scopus bibliometric database were used to evaluate the level of research activity and the scientific community’s interest in MQTT, MQTT-SN, CoAP, STOMP, XMPP, WAMP, AMQP, DDS, OPC UA, and LwM2M protocols. The findings reveal which protocols are at the forefront of contemporary research and hold the most significant potential for further development and implementation in IoT systems. Understanding the current state and prospects of communication protocols provides an essential foundation for developers and researchers to select optimal solutions for IoT systems integration.